Optimal production and characterization of alkaline protease from newly isolated halotolerant Jeotgalicoccus sp. Issue 2 (April 2015) - Mokashe, Narendra; Chaudhari, Ambalal; Patil, Ulhas
Abstract A halotolerant strain UG was newly isolated from saline soil, produces an extracellular alkaline protease. The strain was identified as Jeotgalicoccus sp. on the basis of phylogenetic and phenotypic characteristics. The maximum protease yield (256.4±4.3 U/ml) was attained using optimized medium consists; peptone, K2HPO4, MgSO4·7H2O, CaCl2 and NaCl; pH 10 at 37 °C within 40 h. The protease secretion was calcium ion dependent and enhanced by CaCl2 supplementation in the production medium. A protease produced by Jeotgalicoccus sp. was most active at 48 °C and pH 10. The protease was purified by three step purification pattern which resulted in 39 fold protease purification with a yield of 38%. The molecular weight of purified protease was estimated to be 51 kDa by SDS-PAGE. The protease was inhibited by EDTA, indicating that enzyme belongs to metalloprotease class. Protease showed better activity over a wide range of NaCl (0–1.5 M) and reasonable activity in presence of Ca2+, Mg2+, K+, Mn2+, Cd2+ and Sn2+. Furthermore, the protease was active in the presence of H2O2 and sodium perborate. Also, protease showed the substantial activity in the presence of rhamnolipid and cyclodextrin. The protease from Jeotgalicoccus sp. was suggested as a better bio-additive agent for detergent industry.